Edukasi Imunisasi Dasar Lengkap pada Anak bagi Anggota PKK Wajok Hilir Kecamatan Jongkat Kabupaten Mempawah: Basic Immunization Education in Children for PKK Members at Wajok Hilir, Jongkat District, Mempawah Regency - Ropiqa, Meri; Wahdaningsih, Sri; Nurbaeti, Siti Nani; Rizkifani, Shoma; Agustriangga, Muhammad Rafly; Indriyani, Risa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Immunization is a safe and effective method to protect a person from dangerous diseases before exposure to disease-causing agents. Immunization for children is essential to strengthen the body's defense system so it's immune to disease attacks. Community Service Activities (PKM) aim to equip the Wajok Hilir cadres or PKK mothers with information, education, and skills regarding complete basic immunization information for children. This PKM activity consists of several activities, including designing educational methods, creating complete basic immunization educational media, administering pretest and posttest, and evaluating the level of understanding. The results show that there has been an increase in the understanding of cadres or PKK mothers with the indicator that the average pretest score is 39.58 and the average posttest score is 65.72. The conclusion, there has been an increase in the understanding of the Wajok Hilir cadres or PKK mothers.